Estimating the longitudinal concordance correlation through fixed effects and variance components of polynomial mixed-effects regression model - Oliveira, Thiago de Paula (2018)
In the post-harvest area, a common approach to quantify the average color of fruits peel over time is the sampling of small number of points generally on its equatorial region using a colorimeter. However, when we use a colorimeter to classify an uneven-colored fruit misclassification may occur because points in the peel region may not be representative of average color of fruit. The main problem when we use this method is to determine the number of points to be sampled as well as the location of these points on the fruit\'s surface. An alternative method to evaluate measure of color is digital image analysis because it covers whole of the object surface, by using a sample of pixels taken from the image. As the colorimeter approach is faster and easier than image analysis, it may not be suitable for assessing the overall mean color of the papaya\'s peel and its performance will depend on the number of measured points and choice of sampled region. In this sense, the comparison between these approach is still necessary because we need to know if a sample on the equatorial region can reproduce a sample over the whole region, and if the colorimeter can compete with a scanner or digital camera in measuring the mean hue of papaya peel over time. Thus, we proposed a longitudinal concordance correlation (LCC) based on polynomial mixed-effects regression model to evaluate the extent of agreement among methods. The results show that ideally image analysis of whole fruit\'s region should be used to compute the mean hue and that the topography and curved surface of papaya fruit did not affect the mean hue obtained by the scanner. Since there are still no packages available to estimate the LCC in the free software environment R, we are developing a package called lcc, which provides functions for estimating the longitudinal concordance correlation (LCC) among methods based on variance components and fixed effects of polynomial mixed-effects model. Additionally, we implemented arguments in this function to estimating the longitudinal Pearson correlation (LPC), as precision measure, and longitudinal bias corrector factor (LA), as accuracy measure. Moreover, these components can be estimated using different structures for variance- covariance matrices of random effects and variance functions to model heteroscedasticity among within-group errors using or not the time as variance covariate.